Decomposition of Hydrates under the Action of Ultrahigh-Frequency Radiation - Abdullah, Nashwan; Kutnyi, Bohdan; Leshchenko, Maryna; Shumska, Liubov (International Journal of Engineering and Technology, 2018)
In this work series of field experiments was conducted, a mathematical model was developed and a number of studies were performed to investigate the process of hydrate dissociation under the influence of ultrahigh-frequency radiation. The assumption is implicit that the effect of volumetric sources of heat is the dominant influence on hydration dissociation under the influence of microwave radiation, rather than the effect of boundary conditions. This provision formed the basis of the mathematical modeling of the hydrate massif dissociation. It has been established that processes of heating water, ice melting and snow, and hydrate dissociation occur in a similar way. It is characteristic that the inverse proportional dependence of internal specific heat sources on the volume of material has been obtained, that is, the decrease of the radiator efficiency when the volume of the material is reduced. It is established that volumetric thermal sources occur inside propane hydrate under the influence of microwave radiation.Â